Environmental Policies and Risk Finance in the Green Sector Cross-country Evidence - Criscuolo, Chiara (OECD Science, Technology and Industry Working Papers, 2014)
Start-up firms play a crucial role in bringing to the market the innovations needed to move to a greener growth path. Risk finance is essential for allowing new ventures to commercialise new ideas and grow, especially in emerging sectors. Still, very little is known about the drivers and the characteristics of risk finance in the green sector. This paper aims to fill this gap by providing a detailed description of risk finance in the green sector across 29 OECD and BRIICS countries over the period 2005-2010 and identifying the role that policies might have in shaping high-growth investments in this sector. Results are drawn from a comprehensive deal-level database of businesses seeking financing in the green industry combined with indicators of renewable policies and government R&D expenditures. The results suggest that both supply-side policies and environmental deployment policies, designed with a long-term perspective of creating a market for environmental technologies, are associated with higher levels of risk finance relative to more short-term fiscal policies, such as tax incentives and rebates. In addition, when focusing on renewable energy generation, the results confirm the positive association of generous feed-in tariffs (FITs) with risk-finance investment. However in the solar sector excessively generous FITs tend to discourage investment